Tolerant stories (6). (Journal of Parents and Teachers, 2025)
The article begins with a reflection on tolerance and the importance of bringing people’s perspectives closer together. On the other hand, a series of books are presented, along with their summaries and the topics to be addressed when working with them
Keywords: reflection; letter; tolerance; books